Anatomical relationship between the mandibular foramen and the lateral surface shape of the mandibular ramus using CT. Issue 5 (September 2015) - Goda, Yu; Matsumura, Tatsushi; Yanagi, Yoshinobu; Moritani, Norifumi; Iida, Seiji
Abstract: Objective: The antilingular prominence (AP) is a well-known landmark used during planning of intraoral vertical ramus osteotomy (IVRO) in order to prevent inferior alveolar nerve (IAN) injury, but the location of this landmark is not always clear. In this study, we analyzed the anatomical relationship between the mandibular foramen (MF) and the lateral surface shape of the mandibular ramus for use during IVRO. Patients and methods: We retrospectively analyzed 276 mandibular halves in 67 patients with mandibular deformity and 71 patients without deformity imaged at our department from April 2003 to March 2014. We defined 17 points on the mandibular ramus, and examined the anatomical relationships using multi-planar reconstruction (MPR) images and three-dimensional computed tomography (3DCT) created from preoperative CT data. Results: The prevalence of the AP was 57.6% (159/276) of all cases. The MF was located inferior to the AP in all cases; it was posterior to the AP in 50.3% (80/159) of cases and the sigmoid notch (SN) in 24.6% (68/276) of cases. The minimum horizontal distance between the mandibular posterior ramus border and the MF was 9.28 mm in all cases. Conclusion: The AP cannot always serve as a reference point to prevent IAN damage during IVRO. The osteotomy incision should be placed within 9 mm of the posterior mandibular ramus border in order to prevent intraoperative IAN damage. However, preoperative review of planned osteotomy incisions is necessary in every case.